The Influence of Communication and Counseling Guidance By Teachers on Bullying In Smp Negeri 2 Gunungsitoli Barat - Wansyah Putra Harefa, Ider; Harefa, Idarni; Halawa, Odaligoziduhu; Ndraha, Ayler Beniah (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study explores the influence of communication and counseling guidance on bullying behavior at SMP Negeri 2 Gunungsitoli Barat. Bullying cases in this school are still quite high, with around 60% of students reporting having experienced or witnessed bullying. This study used quantitative and qualitative approaches, with a purposively selected sample of 30 students. Data were collected through observation, questionnaires, and documentation. The results showed that good communication between teachers and students significantly reduced the incidence of bullying. Students with good communication only experienced 5 cases of bullying, while students with poor communication experienced 4 cases out of a total of 5 students. In addition, counseling guidance proved to be effective in dealing with students' emotional problems, although limited human resources were the main obstacle in its implementation. This study emphasizes the importance of effective communication and adequate counseling services as strategies to reduce bullying behavior in schools. The findings are expected to be the basis for better policy formulation in creating a safe and comfortable school environment for all students.